Texture-Modified Soy Protein Gels Using Transglutaminase and Agar for Elderly Dysphagia Management - Puchcharin Paleekui; Benjamard Rattanamato; Nattapong Kanha; Kanyasiri Rakariyatham; Wannaporn Klangpetch; Sukhuntha Osiriphun; Thunnop Laokuldilok (Gels)
Dysphagia, a condition characterized by difficulty swallowing, is commonly found in the elderly, increasing the risk of choking and aspiration. This study aimed to develop a texturally modified soy protein gel that meets the Universal Design Food (UDF) standard, specifically for elderly individuals with dysphagia. To create soft-textured foods, the gel’s texture was modified using transglutaminase at varying concentrations (0.5%, 1.0%, and 2.0%, w/v) in combination with agar. The soy protein gel prepared with 0.5% transglutaminase exhibited the lowest hardness value (2.2 × 103 N/m2) and was classified as Level 4 under the UDF standard, indicating that it requires no chewing and is easy to swallow, making it suitable for individuals with severe dysphagia. In contrast, the gel formulated with 2.0% transglutaminase and 0.5% agar had the highest hardness value (3.29 × 104 N/m2) and was classified as Level 2, meaning it can be easily mashed with the gums, making it appropriate for individuals with moderate dysphagia. Structural analyses revealed that modifying with transglutaminase altered the protein’s secondary structure by reducing the content of α-helixes and β-sheets while increasing β-turns, potentially enhancing gel network flexibility. These findings suggest that the combined use of transglutaminase and agar effectively modifies soy protein gel texture to meet the dietary needs of elderly individuals with dysphagia. This approach shows promise for the food industry by providing safer and more diverse food options for aging populations facing dysphagia.